2015
DOI: 10.1371/journal.pone.0118501
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Differentiation in Seedling Traits in a Hybrid Pine Species Complex, Pinus densata and Its Parental Species, on the Tibetan Plateau

Abstract: Evidence from molecular genetics demonstrates that Pinus densata is a natural homoploid hybrid originating from the parent species Pinus tabuliformis and Pinus yunnanensis, and ecological selection may have played a role in the speciation of P. densata. However, data on differentiation in adaptive traits in the species complex are scarce. In this study, we performed a common garden test on 16 seedling traits to examine the differences between P. densata and its parental species in a high altitude environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Also, there was a strong correlation between NC and BS. It could be that BS relates better to mean annual rainfall in our study, while Meng et al (2015) indicated that annual mean temperature and mean temperature of the coldest month have a stronger relationship with BS in P. yunnanensis over 2 years.…”
Section: Seed Germination and Seedling Traitsmentioning
confidence: 52%
“…Also, there was a strong correlation between NC and BS. It could be that BS relates better to mean annual rainfall in our study, while Meng et al (2015) indicated that annual mean temperature and mean temperature of the coldest month have a stronger relationship with BS in P. yunnanensis over 2 years.…”
Section: Seed Germination and Seedling Traitsmentioning
confidence: 52%
“…Pinus densata is considered a homoploid hybrid speciation (HHS) type species tha originated from the putative parent species P. tabuliformis and P. yunnanensis [14]. The intermediate morphology of pine hybrids is contributed by both parental species, and hy brid derivatives are more similar to the parent with higher genetic contribution, resulting in cryptic introgression [49].…”
Section: Discussionmentioning
confidence: 99%
“…and Pinus yunnanensis Franch. [14]. Evidence from molecular genetics, for example, chloroplast DNA polymorphism [15], allozyme [16][17][18], simultaneous DNA probes of the 18S rRNA gene and the 5S rRNA gene [19], the paternally inherited chloroplast rbcL gene and maternally inherited mitochondrial nad1 fragments [20,21], demonstrates that P. densata is a natural homoploid hybrid and that ecological selection may have played a role in its speciation.…”
Section: Introductionmentioning
confidence: 99%
“…It might also be that trait differences are less apparent in seedlings than in adults (Mediavilla et al., ), since functional traits within an individual can vary drastically among ontogenetic stages (Mason et al., ). Differences in seedling traits of single species have been detected across genotypes within species or hybrid groups, but typically only across genotypes from drastically different environments (Abrams et al., ; Meng et al., ). Still, previous common‐garden and greenhouse studies in Protea have found relationships at early life history stages consistent with field correlations (Carlson et al., , ; Prunier et al., ) as well as evidence for plasticity in leaf size and stomatal traits (Carlson and Holsinger, ).…”
Section: Discussionmentioning
confidence: 99%